Self-disclosure at international cartels - Brenner, Steffen (Journal of International Business Studies, 2011)
We study revelation behavior at illegal international cartels. Our hypotheses suggest that a resource advantage induces executives of large multinational enterprises (MNEs) to be more likely to reveal the cartel and to cooperate with the antitrust agency during the prosecution stage. Moreover, we expect the cultural background to influence the firm's inclination to reveal incriminating evidence. Empirical tests based on data about cartel breakdowns under the EU Leniency Program show that large MNEs are indeed more likely to reveal the cartel. However, they largely fail to explain variation in legal actions along cultural dimensions.